PAYMENT FOR ENVIRONMENTAL SERVICES IN A MUNICIPALITY IN THE STATE OF SÃO PAULO: EQUIVALENT UNIFORM ANNUAL COST - da Silva Fernandes, Jamily [UNESP]; Simões, Danilo [UNESP]; Zakia, Maria José Brito [UNESP]; da Silva, Richardson Barbosa Gomes [UNESP]; de Oliveira, Renata Evangelista (My University, 2024)
The implementation and discussion of Payment for Environmental Services (PES) programs has gained prominence in environmental policy. However, there are still knowledge gaps regarding economic indicators that are fundamental for the analysis of the viability and financing of PES projects. Thus, obtaining information related to the analysis of investment projects in PES programs can contribute to future decision-making. In this context, the objective was to estimate the Equivalent Uniform Annual Cost (EUAC) of investment projects for PES in subwatersheds in the State of São Paulo under conditions of uncertainty, as well as to analyze whether the EUAC allows attesting to the economic viability of these investment projects. From the costs of the PES actions, the EUAC was used and then the Monte Carlo method was applied to incorporate stochastic solutions. The average EUAC of the PES investment projects for the priority and non-priority subwatersheds is USD 1, 814.11 and USD 1, 675.54, respectively. The costs associated with the purchase of organic fertilizer and fence posts have the greatest impact on the EUAC in both the priority and non-priority areas. The EUAC, combined with Spearman's correlation, allows for the analysis of the economic viability of investment projects and thus assists in the decision-making process regarding the prioritization of resource allocation in sub-watersheds.
Pagamento por serviços ambientais em um município do estado de São Paulo: Custo Anual Uniforme Equivalente
Keywords: Economic analysis; Ecosystem services; Water supply